PERLINDUNGAN HUKUM TERHADAP PEREMPUAN PEKERJA SHIFT MALAM DALAM KONTEKS SEXUAL HARASSMENT DI KOTA PEKANBARU - Ridha, Irfan (Faculty of Law Universitas Lancang Kuning, 2020)
Violence against women is any act based on gender-based distinctions that result or may result in suffering for women physically, sexually, or psychologically, including the threat of such acts, coercion, or arbitrary freedom deprivation, Whether occurring in public spaces or personal life. The paper's result is empirical research using data collection methods based on field surveys and interviews. There are still many cases of violence in the context of sexual harassment against women, especially against women who work at night. So, to guarantee legal certainty and justice, it is recommended that law enforcement efforts are more emphatically in protecting women's rights.